Active Labour Market Measures in Serbia – Challenges and Results - Vuković, Drenka; Perisić, Natalija (Ревија за социјална политика/Journal of Social Policy, 2012)
Transition changes in Serbia were followed by profound political, economic and social problems. After the „democratic changes“ of 2000 progress has been made in providing macro-economic stability and economic reforms, but the labor market situation is still unfavorable. Restructuring of economy and unsuccessful privatization have resulted in reduced employment and increased unemployment, while young, women, people with secondary-school qualifications, disabled, refugees and internally displaced persons, certain ethnic minorities and rural inhabitants are especially exposed to risk of staying without jobs. Negative effects of the global economic crisis have triggered the problem of lack of an adequate employment policy and shortage of ALMP. Programmes of active and passive labour market measures have been created pursuant to legal regulations and available financial resources. The number of beneficiaries of cash benefits has been constantly increasing. Expenditures for ALMP have been modest and insufficient for the realization of ambitious programmes. Researches of the results of ALMP implementation in the previous period have pointed to limited effects and inadequate coverage of the unemployed.The labor market has been reformed according to general strategic orientations, specific national situation and challenges of the European integration. New laws have been enacted, as well as strategies for the periods 2005-2010and 2011-2020 along with the action plans. Strategic orientations have been clearly defined with an emphasis on greater expenditures for ALMP, but it was not realized in practice in full. New wave of recession has resulted in additional reduction of costs for ALMP, which will impact the realization of ambitiously projected aims pursuant to „Europe 2020“.
Keywords: labour market; employment; unemployment; passive and active measures; strategc aims; risks and limitations